Correlation analysis of Singaporean land reclamation towards its national population - Akmalhisham Jasni; Sharifah Munirah Alatas; Sharifah Mastura Syed Abdullah (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2015)
Land reclamation is a technique that refers to sand dredging in a given location and the sand is then placed at another location by the shores to elevate the seabed surface level until it becomes a new landscape. Among the countries that actively embark into land reclamation activities in the South East Asian region is Singapore. This is because, Singapore is one of the countries which experience land insufficiency and have a limited coastal area. This study has focused the pattern of Singaporean population, and to identify its relevance to the land reclamation objectives. The collection of primary information was done through direct site observation, and through several interviews. Meanwhile, the collection of secondary materials was done using the library study method in relevant premises. The step taken by Singapore to reclaim its territories is not only because of the increased population alone. This study finds that the number of Singaporean native citizens’ population has declined over the years based on the total fertility rate (TFR) of its natives. This is due to the fact that although Singapore has implemented land reclamation up until today, the latest statistics of population issued by the National Population and Talent Division, Prime Minister’s Office in Singapore has recorded a drop of the TFR for its people to 1.19 point, and stays under the level of 2.10 point for the past 30 years. Thus this study has found that, there is no any relationship can be established between the land reclamation activities towards its population issues in Singapore.